Monetary behaviour of students from different countries - Chang, Xiaohui; Fofanova, Galina A. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
It is pointed out that modern students face a variety of financial challenges that have a significant impact on them and shape their monetary behaviour. It is noted that the concept «monetary behaviour» refers to a set of actions and decisions related to the management of personal funds (budget planning, savings and investment, use of credit, etc.), as well as attitudes towards money. Financial actions of young people from different countries, in particular from China, Russia and Belarus, are compared. It is revealed that differences in the money habits of student representatives are due to social and economic conditions, digitalisation, cultural traditions and their level of financial literacy. Ways to improve the monetary behaviour of young people are outlined.
Keywords: monetary behaviour; students; financial literacy; loans; digitalisation; cultural differences; economic conditions